THE ROLE OF TRADITIONAL POLITICAL LEADERS IN THE URBAN DEVELOPMENT OF ISANLU KINGDOM UNDER OBA IBRAHIM AGBANA AGIE, 1935 - 1971 - Ayorinde Emmanuel Moses (International Studies Journal)
This study is an assessment of the contribution of Oba Ibrahim Agbana Agie to urban development in Isanlu Kingdom between 1935 and 1971. The objectives of the study were to: The Traditional Leadership Institutions have remained an imperative heritage in Nigeria, the roles that Traditional leaders played in Urban development of the Country is tremendous. One of the traditional authorities that have not been given adequate documentation is the role played by Oba Ibrahim Agbana Agie in bringing to place the present day Isanlu Kingdom in Yagba East L.G.A. of Kogi State.